1989
DOI: 10.1128/jb.171.6.3568-3571.1989
|View full text |Cite
|
Sign up to set email alerts
|

Formation of crystals of the insecticidal proteins of Bacillus thuringiensis subsp. aizawai IPL7 in Escherichia coli

Abstract: Escherichia coli JM103 cells harboring expression plasmid pTB1 or pKC6 synthesized the 130-and 135-kilodalton insecticidal proteins, respectively, of BaciUus thuringiensis subsp. aizawai IPL7, and both products accumulated as cytoplasmic inclusion bodies. Amorphous inclusions which contained contaminating proteins, together with the corresponding insecticidal proteins, were formed in cultures at 37°C, but bipyramidal crystals practically free of contaminants were observed at 30°C. Although 9.8% of the amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Oeda et al (26) reported that when E. coli contained a plasmid with the gene for the 8 endotoxin of B. thuringiensis var. aizawai, temperature determined the appearance of the inclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Oeda et al (26) reported that when E. coli contained a plasmid with the gene for the 8 endotoxin of B. thuringiensis var. aizawai, temperature determined the appearance of the inclusions.…”
Section: Discussionmentioning
confidence: 99%
“…aizawai which were produced and accumulated in the recombinant Escherichia coli JMI03. 21 ) The inclusions contained CryIA(a) or CryIA(b) in almost the same amount (Fig. 1, lanes 2 and 3).…”
Section: In Vitro Solubilization and Digestion Of Inclusionsmentioning
confidence: 99%
“…The CrylC e~stals produced from the E. coli recombinant at 37 ° C were predonfinantly amorphous shaped (not shown), possibly due to temperature effects on protein assembly (29). Other groups also have documented the presence of small peptides associated with various toxins expressed in recombinant E. coil (10,27,29). Eater fractions contained CryIC purified to a single protein band as determined by SDS-PAGE.…”
Section: Discussionmentioning
confidence: 94%
“…The CrylC e~stals produced from the E. coli recombinant at 37 ° C were predonfinantly amorphous shaped (not shown), possibly due to temperature effects on protein assembly (29). The CrylC e~stals produced from the E. coli recombinant at 37 ° C were predonfinantly amorphous shaped (not shown), possibly due to temperature effects on protein assembly (29).…”
Section: Discussionmentioning
confidence: 97%